2013
DOI: 10.1155/2013/104059
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Renal Effects of Bromocriptine in Diabetic Patients with Stage 4 Chronic Kidney Disease

Abstract: Objective. The objective of this study was to investigate the effect of bromocriptine (BEC) on left ventricular mass index (LVMI) and residual renal function (RRF) in chronic kidney disease (CKD) patients with type 2 diabetes (T2D). Research Design and Methods. A 6-month double-blind randomized controlled trial was conducted in 28 patients with T2D and stage 4 CKD with increased LVMI. Fourteen patients received BEC (2.5 mg, initially 1 tablet with subsequent increase to three times a day) and 14 received a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The prevalence of cardiovascular death in CKD patients, especially in those on dialysis therapy, is 10-20 times greater than the age-, gender-, and race-matched general population [15,16]. Some studies have demonstrated that atherosclerosis could induce the increase of the arterial IMT and arterial stiffening, and eventually lead to luminal obstruction with consequent ischemic events, such as myocardial infarction and stroke [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cardiovascular death in CKD patients, especially in those on dialysis therapy, is 10-20 times greater than the age-, gender-, and race-matched general population [15,16]. Some studies have demonstrated that atherosclerosis could induce the increase of the arterial IMT and arterial stiffening, and eventually lead to luminal obstruction with consequent ischemic events, such as myocardial infarction and stroke [17,18].…”
Section: Discussionmentioning
confidence: 99%
“… 31 In a randomized controlled trial 6-month treatment with BROM-QR in 28 patients with T2DM, a decrease in blood pressure and left ventricular mass was reported, while creatinine clearance remained unchanged. 32 …”
Section: Discussionmentioning
confidence: 99%
“…As shown by the results of clinical trials and experiments with hypertensive rats, dysfunctions in the cardiovascular system can be a good reason to use BC in the treatment of T2DM and MS [212,232]. In addition, BC prevents the abnormalities in the excretory system of diabetic patients and in the case of chronic kidney diseases slows down their progress [239]. …”
Section: Dopamine Signaling Systemmentioning
confidence: 99%